RANCANG BANGUN SMART-HOME (APLIKASI INSTALASI PERANGKAT ENERGI ALTERNATIF SINAR MATAHARI DALAM DISAIN RUMAH TINGGAL) - Pribadi, Septana Bagus; Prianto, Eddy (MODUL, 2018)
The development of non-polluted renewable energy such as solar power, wind power, hydro power, sea wave power, growed rapidly in accordance with the technology developments in the recent decade.The electric energy from PLN (Indonesian Electricity Company) obtained from fuels processed through power plant converted into electrical energy. Generally, the use of electricity as a major power generator causes pollution, besides the price of fossil fuels tends to rise that make the increase in investment. One of abundantly alternative energy in Indonesia is solar radiation. The employing of of solar energy used solar panels (solar cell) convert sunlight into electrical energy directly. It easily employs in residencies commonly referred to Solar Home System.The synergistic home design which applies active design tools called Smart Home. As the development of a power plant has no synchronization with the residential design, this research purposes to observe and synchronize the installation of alternative energy device in residencies.The cooperation with PT ATMI Kreasi Energy was very advantageous for developing this subject matter from other perspectives in the future.